Establishment of Safety Evaluation Factors for Dust Storms in the Landing Area Selection for Tianwen‐3 Mission - Puzheng Wen; Yuan Tian; Bo Li; Shaojie Qu (Earth and Space Science)
Abstract China's Tianwen‐3 mission is expected to be launched around 2028, making it the first Mars sample return mission. Dust storms occurring in all seasons on Mars can affect the accuracy and safety of the landing and takeoff phases of Mars sampling missions. Hence, analyzing the spatio‐temporal patterns of dust storms in the landing areas is important for the success of the Tianwen‐3 mission. In this paper, firstly we improved the engineering constraints for selecting Mars landing sites (Golombek et al., 2012) by adding safety evaluation factors of dust storm activity. There are three factors: the emergence of protogenous dust storms, a dust storm sequence passing through and the buffer time of dust storm sequence. The pre‐selected landing areas in Utopia and Chryse Planitia of Tianwen‐3 mission can be divided into three categories: danger zones (areas with protogenous dust storm activity), safety zones (areas without any dust storm occurrence), and forecast zones (areas without protogenous dust storm activity but with dust storm sequences passing through). Then, the safety evaluation factors and method for predicting dust storms proposed in this paper have been successfully applied to the landing process of Tianwen‐1 and their correctness has also been verified. Finally, taking into account factors such as elevation, slope, dust storm safety and scientific values, we selected four priority landing sites from the 40 pre‐selected landing sites for Tianwen‐3 mission.